38 Risk of endometrial cancer among women with benign ovarian tumors – a danish nationwide cohort study. (4th December 2020) - Reinholdt, Kristian; Kjær, Susanne Krüger; Guleria, Sonia; Frederiksen, Kirsten; Mellemkjær, Lene; Munk, Christian; Jensen, Allan
Abstract : Introduction/Background: The few studies investigating a potential association between benign ovarian tumors and endometrial cancer have been inconclusive. Using data from a large Danish register-based cohort study, we assessed the overall and type-specific risk of endometrial cancer among women with a benign ovarian tumor. Methodology: We identified all Danish women diagnosed with a benign ovarian tumor during 1978–2016 in the Danish National Patient Register (n = 149, 807). The study population was followed for subsequent development of endometrial cancer by linkage to the Danish Cancer Register and standardized incidence ratios (SIRs) with corresponding 95% confidence intervals (CIs) were calculated after correction for hysterectomy. Results: Women with benign ovarian tumors had a decreased incidence of endometrial cancer (SIR = 0.74, 95% CI: 0.68–0.81) compared with women in the general Danish female population. Both solid benign ovarian tumors (SIR = 0.79, 95% CI 0.70–0.88) and cystic benign ovarian tumors (SIR = 0.68, 95% CI 0.58–0.78) were associated with decreased incidences of endometrial cancer. Likewise, women with benign ovarian tumors had decreased incidences of both type I and type II endometrial cancer. The incidence of endometrial cancer was decreased to virtually the same magnitude irrespective of the age at diagnosis of a benign ovarian tumor and the reduction persisted for up to 20+ years after the ovarian tumor diagnosis. Conclusion: The risk of endometrial cancer was decreased beyond the first year after a benign ovarian tumor and the decrease persisted for 20 or more years. The possible underlying mechanisms are not known and should be investigated further. Disclosures: None.